Wijsman Orlicz Asymptotically Ideal ϕ-Statistical Equivalent Sequences. (28th October 2013) - Hazarika, Bipan
Abstract : An ideal I is a family of subsets of positive integers ℕ which is closed under taking finite unions and subsets of its elements. In this paper, we introduce a new definition of asymptotically ideal ϕ -statistical equivalent sequence in Wijsman sense and present some definitions which are the natural combination of the definition of asymptotic equivalence, statistical equivalent, ϕ -statistical equivalent sequences in Wijsman sense. Finally, we introduce the notion of Cesaro Orlicz asymptotically ϕ -equivalent sequences in Wijsman sense and establish their relationship with other classes.